REINFORCEMENT NILAI-NILAI PENDIDIKAN MULTIKULTURAL DALAM PEMBELAJARAN PAI BUDI PEKERTI STUDI KASUS DI SD CANDIRENGGO SINGOSARI - M. Nur Zuhri Fauzi; Ahmad Marzuki (Journal Multicultural of Islamic Education, 2021)
Reinforcement is the reinforcement of behavior that can result in the behavior being repeated. Therefore, reinforcement can be used as a way to achieve good behavior in learning. This study uses a qualitative method with a case study approach. While the data collection techniques are in-depth interviews, participatory observation, and documentation. And the research subjects are school principals, PAI teachers, community leaders. Basically the reinforcement at Candirenggo Elementary School uses two types. Verbal reinforcement, namely by using words of encouragement that are inserted when the activity is right after the dhuha prayer at the time of mauidhotul hasanah. And non-verbal reinforcement plus verbal, namely by approaching students and providing an encouragement. How to use it in several ways, including reinforcement to certain individuals, namely to students who need certain handlers such as when practicing lesson 6, strengthening to groups of students, namely when several groups have succeeded in answering questions and have carried out dramas. And using several principles of strengthening or reinforcement including warmth and enthusiasm when students carry out the dhuha prayer to completion, meaningfulness when listening to cults or mauidhotul hasanah.